Phytoremediation of Nutrients and Organic Carbon from Sago Mill Effluent using Water Hyacinth (Eichhornia crassipes) - Nash, Daniah Ali Hassoon; Abdullah, Siti Rozaimah Sheikh; Hasan, Hassimi Abu; Mushrifah, Idris; Muhammad, Nurul Fadhilah; Al-Baldawi, Israa Abdulwahab; Ismail, Nur ?Izzati (Journal of Engineering and Technological Sciences, 2019)
The aim of this study was to investigate the ability of floating water hyacinth (Eichhornia crassipes) to survive under selected concentrations of sago mill effluent (SME) and determine the nutrient uptake by the plant. Phytoremediation at 10, 15, and 20% (VSME/Vwater) SME concentrations by water hyacinth was conducted under greenhouse conditions for 30 d in a batch type experiment. After 30 d of phytoremediation, the removal efficiency of chemical oxygen demand, ammonia and phosphorus from SME wastewater were (86.4% to 97.2%), (91.4% to 97.3%) and (80.4 to 97.2%), respectively. The results proved the efficiency of water hyacinth to polish SME wastewater.